Time Management Assistance in Developing Superior Human Resources - Sopanah, Ana; Rusdianti, Imanita Septian; Sulistyan, Riza Bahtiar; Khasanah, Midhatul (Trescode Green Organization, 2025)
This study aims to improve the effectiveness of employee time management through training and mentoring at PT Kasih Jaya Sejahtera, Malang Regency. The method used was a qualitative approach with data collection techniques in the form of in-depth interviews with company owners, operational workers, and HR managers, as well as field observations from January to March 2025. The results of the activities showed an increase in employee ability to set work priorities, adherence to schedules, and efficiency in completing daily tasks. In addition, unique implementations such as the